On-Line Monitoring Shaft Misalignment of Feed Drive Systems Based on Time-Domain Shaft Rotating Holospectrum - Y. S. Chiu; C. C. Cheng; W. C. Hsu; M. H. Huang (Shock and Vibration)
Detection of early-stage misalignment of the ball screw in feed drive systems is the topic addressed in this study. The triaxial vibration amplitudes and phases of a rotating ball screw at the ball screw nut were extracted using the Vold–Kalman filtering order tracking (VKFOT). The rotating ball screw locus at the rotation speed and its multiplier in the time domain were then constructed to obtain corresponding holospectra. By using a self-organizing map, the features corresponding to various holospectra were extracted and quantified into metrices as a measure signifying the severity of ball screw misalignment. Experimental results indicated that the proposed method effectively detected the ball screw misalignment even though this misalignment was less than 30 μm in size. The experiments conducted in this study demonstrated the high sensitivity and effectiveness of the proposed method, which also has a clear advantage due to its simpler instrumentation compared with traditional accelerometry.